Plan de Negocios para Productos Turísticos de la Finca “San Gabriel”, Comunidad San Gabriel, Parroquia Yangana, Cantón Loja - Abad Abad, Leidy Susana (2017)
This thesis work is based on a "Business Plan for tourism products of the estate" San Gabriel, San Gabriel community, Yangana parish, Loja canton ", as an alternative to the negative incidence of lack of services and tourist activities And to help promote and encourage tourism on the farm and in the Yangana parish. The analysis of the thesis was determined by the following objectives:To make a diagnosis of the current situation of the farm, it was possible to know the current situation of the external and internal area of the farm; To carry out a proposal of tourist products for the estate San gabriel, it is executed by means of the market, technical, administrative, legal, environmental and financial study; Socializing the Business Plan with the owner, authorities and community, was able to publicize the proposal obtaining opinions and suggestions that helped with the strengthening of research development. For the accomplishment of the research work the analytical, scientific, deductive and inductive method was used; Techniques such as direct observation, survey, interview and bibliographic review. In addition, the tourist inventory sheets and the SWOT Matrix were used to detect the strengths, weaknesses, opportunities and threats of the company, and then carry out the Strategy Matrix. Within the results can be determined that the Finca San Gabriel has a great tourist potential to develop, being the Business Plan a guide for the implementation of the project, and a very beneficial form of investment since the profits to be obtained will be profitable During its useful life, in order to implement the project, an amount of $ 60,445.02 was required to establish the feasibility of the project, the following indicators were analyzed: cash flow, net present value (NPV) with a value of $ 48,661 , 98, the internal rate of return (TIR) with 36.01%, the benefit / cost ratio (RBC) is $ 2.64, meaning that for every dollar invested the company earns $ 1.64 dollars, and the recovery period Of capital (PRC) will be in 3 years, 10 months and 27 days; The sensitivity analysis indicates that the project supports a cost increase of 61.00% and a reduction of revenues with 23.50%, with a result of 0.99 which indicated that the project is favorable. Finally, the conclusions and recommendations of the project were culminated, the bibliography consulted, the index and the respective annexes that support the procedure of the present work are described.